Two New Isoprenoid Flavonoids from Sophora flavescens with Antioxidant and Cytotoxic Activities - Jingjing Li; Yan Lin; Lei He; Rongxiu Ou; Tao Chen; Xu Zhang; Qirui Li; Zhu Zeng; Qingde Long (Molecules, 2021)
Sophora flavescens is a regularly used traditional Chinese medicine. In an attempt to discover adequate active agents, the isoprenoid flavonoids from S. flavescens were further investigated. In this work, two new compounds (1–2, kurarinol A-B) together with 26 known ones (3–28) were isolated and elucidated on the basis of extensive NMR, UV and MS analyses. Furthermore, the antioxidant activity of all constituents was assessed through ABTS, PTIO and DPPH methodologies and also were evaluated for cytotoxic activity by three tumor cell lines (HepG2, A549 and MCF7) and one human normal cell line (LO2 cells). As a result, a multitude of components revealed significant inhibitory activity. In particular, compound 1–2 (kurarinol A-B), two new flavanonols derivatives, exhibited the most potent ABTS inhibitory activity with IC50 of 1.21 µg/mL and 1.81 µg/mL, respectively. Meanwhile, the new compound 1 demonstrated remarkable cytotoxicity against three cancer cells lines with IC50 values ranging from 7.50–10.55 μM but showed little effect on the normal cell. The two new isoprenoid flavonoids could be promising antioxidant and anti-tumor nature agents.